Preparation method of heat-conducting composite filler and heat-conducting composite material
The thermally conductive composite filler is prepared by combining gallium indium alloy with boron nitride nanosheets, which solves the fluidity and corrosion problems of gallium-based liquid metals, improves the thermal conductivity efficiency of boron nitride-based materials, and realizes the preparation of high-performance thermally conductive composite materials. Excellent thermal conductivity and reliability.
Patent Information
- Application Number
- CN202411594044.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, gallium-based liquid metals have fluidity and corrosion problems in thermally conductive materials, resulting in limited use in large-scale applications, and the thermal conductivity efficiency of boron nitride-based polymer composites is insufficient, making it difficult to meet the high-performance thermal conductivity requirements. .
Thermal conductivity composite filler is prepared by combining gallium indium alloy with boron nitride nanosheets. Through ultrasonic peeling and interface modification technology, a highly thermally conductive gallium indium alloy with boron nitride nanosheets is formed, and combined with polyurethane to prepare the thermal conductivity filler. High-performance thermal composite material.
It significantly improves the thermal conductivity efficiency of thermal composite materials and the thermal conductivity under deformation states, enhances the compatibility and reliability of materials, and provides better thermal conductivity and greater potential value.
Smart Images

Figure CN119264519A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparing thermal conductive fillers by boron nitride, and specifically relates to a method for preparing thermal conductive composite fillers by combining a high thermal conductive gallium-indium alloy with boron nitride nanosheets and a method for preparing a thermal conductive composite material. Background Art
[0002] With the improvement of the performance of high-power microelectronic devices, the integration of components and the miniaturization of size, the waste heat generated by the devices during operation not only affects the performance and life of the devices, but also inevitably interferes with the functions of other nearby devices. Therefore, the heat dissipation of electronic components is an important issue that needs to be solved urgently. The demand for the development of electronic heat dissipation materials is growing, and boron nitride (BN)-based polymer composites have become advanced composite materials due to their high temperature and good electrical insulation. Hexagonal boron nitride (BN) has high thermal conductivity (in-plane TC ~ 400W m -1 K -1 As high as metal, TC~30W m -1 K -1 ), excellent electrical insulation properties (1013-1015·Q·cm) and high-quality mass production make it a promising thermal conductive filler. Hongyu Niu et al. prepared BN film-filled silicone rubber composites by a simple stacking-cutting method, which maintained the high orientation of the BN film and thus achieved a record high thermal conductivity of 19.1 W m -1 K -1 The high pass surface and low compression modulus of 5.42 MPa. The low BN content (37.vo1%) ensures the softness and elasticity of the preparation.
[0003] Gallium-based liquid metal has attracted more and more attention as a thermal interface material due to its flexibility, relatively high thermal conductivity and low resistance. Liu Han et al. combined AIN with liquid metal (LM,·Ga 68.5 In 21.5 Sn 10 )) and one of the most commonly used silicone oils, polydimethylsiloxane (PDMS), were combined to enhance interfacial heat transfer, and a new composite thermal interface material (TIM) was synthesized. Gallium-based liquid metal has, but it also has inherent defects, such as its good fluidity, which easily leads to leakage, and is easy to corrode with the contacting metal, which hinders large-scale application.
[0004] Gallium-based liquid metal and boron nitride (BN)-based polymer composites represent an emerging material structure that exhibits unique mechanical response flexibility and thermal functions, improves its reliability in use, and has great potential value in the field of thermal conductivity. Therefore, the preparation and thermal conductivity research of liquid metal and boron nitride (BN)-based polymer composites is of great significance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a thermally conductive composite filler and a method for preparing a thermally conductive composite material in view of the deficiencies in the above-mentioned prior art, wherein the thermally conductive composite filler is prepared by composite of gallium-indium alloy liquid metal and boron nitride nanosheets, has high thermal conductivity, effectively improves the thermal conductivity efficiency of boron nitride, and has excellent thermal conductivity effect. At the same time, the thermally conductive composite material is prepared by the thermally conductive composite filler. The deformation process of the thermally conductive composite material under the tensile state can improve the thermal conductivity of the composite material under the deformation state, and effectively dissipate the tensile stress. Thanks to the interface modification of the gallium-indium alloy microspheres, the compatibility between the thermally conductive composite filler and the thermally conductive composite material substrate can be improved; the thermally conductive composite filler and the thermally conductive composite material have high reliability in use and have huge potential value in the field of thermal conductivity.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0007] A method for preparing a thermally conductive composite filler comprises the following steps:
[0008] Step (1), preparation of boron nitride nanosheets BNNSs:
[0009] (1.1) Hexagonal boron nitride (BN) is placed in a mixed solvent of N,N-dimethylformamide (DMF) and distilled water in a certain proportion, an interfacial intercalation agent is added, and ultrasonic exfoliation is performed. After that, the boron nitride nanosheets (BNNSs) after ultrasonic exfoliation are collected by filtration, rinsed, and dried for later use;
[0010] Step (2), blend preparation:
[0011] (2.1) Gallium-indium alloy LM is placed in distilled water, and an interface modifier is added to obtain a blend;
[0012] (2.2) Ultrasonicate the blend for a period of time, remove a certain volume of the upper layer of the blend when the ultrasound is stopped, and then inject distilled water with the same volume of the removed clear liquid into the blend;
[0013] (2.3) Repeat step (2.2) multiple times, and finally retain a certain volume of the blend;
[0014] Step (3), preparation of the composite thermal conductive filler LM-BNNSs of gallium-indium alloy and boron nitride nanosheets:
[0015] (3.1) The last retained blend in step (2.3) is mixed with boron nitride nanosheets BNNSs in a container in proportion, and the mixture is mixed and stirred in an aqueous phase under a certain temperature environment to cause the gallium-indium alloy LM to adhere to the surface of the boron nitride nanosheets BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs, referred to as a thermal conductive composite filler, is obtained.
[0016] As a further improved technical solution of the present invention, the step (1) is specifically:
[0017] 5 g of hexagonal boron nitride BN was placed in 100 mL of a mixed solvent of N,N-dimethylformamide DMF and distilled water in a certain proportion, 4 mL of an interfacial intercalation agent was added, and ultrasonic stripping was performed at room temperature for 4 hours at a power of 500 W. After that, the boron nitride nanosheets BNNSs after ultrasonic stripping were collected by filtration, rinsed with distilled water, and dried at 60°C for use.
[0018] As a further improved technical solution of the present invention, in the step (1), the co-blended solvent is a mixed solution of N,N-dimethylformamide DMF and distilled water in a volume ratio of 1:1-3.
[0019] As a further improved technical solution of the present invention, in the step (1), the interfacial intercalant is one of the diol solvents such as hexanediol.
[0020] As a further improved technical solution of the present invention, the step (2) is specifically as follows:
[0021] (2.1), 1 g of gallium-indium alloy LM was placed in 20 mL of distilled water, and 1.5 g of interface modifier was added to obtain a blend;
[0022] (2.2) Ultrasonicate the blend for 30 minutes at 100% power using a 600W probe, specifically in a 15-second on and 15-second off mode; remove 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend when the ultrasound is stopped;
[0023] (2.3) Repeat step (2.2) 3-4 times, and finally retain 10 mL of the blend.
[0024] As a further improved technical solution of the present invention, in the step (2), the gallium-indium alloy LM is gallium-indium or gallium-indium-tin, wherein the mass ratio of gallium is above 60%.
[0025] As a further improved technical solution of the present invention, in the step (2), the interface modifier is one of polythioureas such as 2,5-dithiodiurea and thiourea.
[0026] As a further improved technical solution of the present invention, the step (3) is specifically as follows:
[0027] The last retained blend in step (2.3) is mixed with boron nitride nanosheets BNNSs in a container in proportion, and the mixture is mixed and stirred in an aqueous phase at 60°C for 2 hours to cause the gallium-indium alloy LM to adhere to the surface of the boron nitride nanosheets BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs is obtained.
[0028] As a further improved technical solution of the present invention, in the step (3), the gallium-indium alloy LM and the boron nitride nanosheets BNNSs are blended in proportion to a mass ratio of 1:2-3, wherein the mass of the gallium-indium alloy LM in the blend is the gram weight of the gallium-indium alloy LM in step (2.1).
[0029] In order to achieve the above technical purpose, another technical solution adopted by the present invention is:
[0030] A method for preparing a thermally conductive composite material prepared from a thermally conductive composite filler, comprising:
[0031] Dissolving polyurethane in a benign solvent, stirring at a certain temperature until the polyurethane is completely dissolved, to obtain a polyurethane solution;
[0032] Adding the gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs into the polyurethane solution, stirring, then transferring to a planetary disperser for dispersion, taking out, and obtaining a dispersed and mixed mixture;
[0033] Deionized water is added to the dispersed and mixed mixture under stirring to promote the precipitation of the thermally conductive polyurethane composite material. The precipitated thermally conductive polyurethane composite material is dried and hot-pressed to obtain a formed thermally conductive polyurethane composite material, referred to as a thermally conductive composite material.
[0034] The beneficial effects of the present invention are:
[0035] The invention discloses a method for preparing a thermally conductive composite filler and a method for preparing a thermally conductive composite material, wherein the thermally conductive composite filler is prepared by compositely preparing gallium-indium alloy liquid metal and boron nitride nanosheets, belongs to a thermally conductive composite filler, has high thermal conductivity, effectively improves the thermal conductivity efficiency of a single boron nitride nanosheet, and has an excellent thermal conductivity effect; at the same time, the thermally conductive composite material is prepared by the thermally conductive composite filler, and the deformation process of the thermally conductive composite material under a tensile state can improve the thermal conductivity of the composite material under a deformed state, and effectively dissipate tensile stress; thanks to the interface modification of gallium-indium alloy microspheres, the compatibility between the thermally conductive composite filler and the thermally conductive composite material substrate can be improved; the thermally conductive composite filler and the thermally conductive composite material have high reliability in use, have huge potential value in the field of thermal conductivity, and are of great significance.
[0036] At the same mass ratio of thermally conductive filler, the thermal conductivity of the composite thermally conductive filler containing gallium-indium alloy liquid metal and boron nitride nanosheets BNNSs of the present invention is significantly higher than that of a single boron nitride nanosheet BNNSs filler. The gallium-indium alloy droplets have a significant bridging effect between BNNSs, thereby optimizing the phonon transmission channel. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The SEM and SEM-mapping images of the thermally conductive composite filler prepared in Example 4 of the present invention.
[0038] Figure 2 This is a comparison chart of the in-plane thermal conductivity of the thermally conductive polyurethane composite material prepared from 400-micron boron nitride nanosheets (BNNSs) in Comparative Example 1 of the present invention and the thermally conductive polyurethane composite material prepared from a composite thermally conductive filler of gallium-indium alloy and boron nitride nanosheets (referred to as thermally conductive composite filler, LM-BNNSs) in Example 4. DETAILED DESCRIPTION
[0039] The specific embodiments of the present invention are further described below according to the accompanying drawings:
[0040] Embodiment 1:
[0041] (1) 5 g of hexagonal boron nitride (BN) was placed in a mixture of 100 mL of N,N-dimethylformamide (DMF) and distilled water in a ratio of 1:3 (volume ratio), 4 mL of intercalation agent hexanediol was added, and ultrasonic exfoliation was performed at room temperature for 4 hours at a power of 500 W. The boron nitride nanosheets (BNNSs) after ultrasonic exfoliation were collected by filtration, rinsed with distilled water, and dried at 60 °C for later use;
[0042] (2) 1 g of gallium-indium alloy (gallium-indium, gallium mass ratio is 62%) is placed in 20 mL of distilled water, and 1.5 g of interface modifier 2,5-dithiodiurea is added to obtain a blend.
[0043] Ultrasonicate the blend for 30 minutes at 100% power of 600W probe ultrasound (15 seconds on, 15 seconds off working mode), remove 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend in the stop ultrasound state, repeat this process 3-4 times, and finally retain about 10 mL of the blend;
[0044] (3) The last remaining blend in step (2) is mixed with BNNSs in a container in proportion (specifically, the mass ratio of gallium indium to boron nitride nanosheets BNNSs in the blend is 1:2.2, wherein the mass of gallium indium in the blend is the gram weight of gallium indium in step (2), i.e., 1 g). The mixture is mixed and stirred in an aqueous phase at 60° C. for about 2 h to cause gallium indium to adhere to the surface of BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs), referred to as a thermal conductive composite filler, is obtained.
[0045] The prepared gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler and polyurethane are mixed in a ratio of 7:3 to prepare a thermal conductive polyurethane composite material containing 30wt% thermal conductive composite filler, referred to as a thermal conductive composite material. The preparation method is as follows: 7g of polyurethane is dissolved in its benign solvent (DMF), the amount of solvent is not more than about 2 times the volume of polyurethane, and stirred at 60°C until the polyurethane is completely dissolved, and 3g of gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs is added to the polyurethane solution, stirred for about 30 minutes, transferred to a planetary disperser and dispersed for 30 minutes at 500 rpm, and taken out. The above-mentioned dispersed and mixed mixture is added with deionized water about 4 times the volume of the polyurethane solvent under stirring at 300 rpm to promote the precipitation of the thermal conductive polyurethane composite material. The precipitated thermal conductive polyurethane composite material is dried and hot-pressed for use. (The preparation method of other thermal conductive composite materials containing different mass fractions of thermal conductive composite fillers is the same as the above, only the corresponding mass of the thermal conductive composite filler is changed).
[0046] Embodiment 2:
[0047] (1) 5 g of hexagonal boron nitride (BN) was placed in a mixture of 100 mL of N,N-dimethylformamide (DMF) and distilled water in a ratio of 1:1 (volume ratio), 4 mL of intercalation agent hexanediol or other diol solvents were added, and ultrasonic peeling was performed at room temperature for 4 hours at a power of 500 W. The boron nitride nanosheets (BNNSs) after ultrasonic peeling were collected by filtration, rinsed with distilled water, and dried at 60°C for later use;
[0048] (2) 1 g of gallium-indium alloy (gallium-indium, gallium mass ratio is 62%) is placed in 20 mL of distilled water, and 1.5 g of an interface modifier such as 2,5-dithiodiurea, thiourea or other polythiourea is added to obtain a blend.
[0049] Ultrasonicate the blend for 30 minutes at 100% power of 600W probe ultrasound (15 seconds on, 15 seconds off working mode), remove 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend in the stop ultrasound state, repeat this process 3-4 times, and finally retain about 10 mL of the blend;
[0050] (3) The last remaining blend in step (2) is mixed with BNNSs in a container in proportion (specifically, the mass ratio of gallium indium to boron nitride nanosheets BNNSs in the blend is 1:2, wherein the mass of gallium indium in the blend is the gram weight of gallium indium in step (2), i.e., 1 g). The mixture is mixed and stirred in an aqueous phase at 60° C. for about 2 h to cause gallium indium to adhere to the surface of BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs), referred to as a thermal conductive composite filler, is obtained.
[0051] The prepared gallium-indium alloy was mixed with the boron nitride nanosheet composite thermal conductive filler and polyurethane in a ratio of 7:3 to prepare a thermally conductive polyurethane composite material containing 30 wt % of the thermally conductive composite filler, referred to as the thermally conductive composite material. The preparation method was the same as that in Example 1.
[0052] Embodiment 3:
[0053] (1) 5 g of hexagonal boron nitride (BN) was placed in a mixture of 100 mL of N,N-dimethylformamide (DMF) and distilled water in a ratio of 1:2.5 (volume ratio), 4 mL of intercalation agent hexanediol was added, and ultrasonic stripping was performed at room temperature for 4 hours at a power of 500 W. The boron nitride nanosheets (BNNSs) after ultrasonic stripping were collected by filtration, rinsed with distilled water, and dried at 60 °C for later use;
[0054] (2) 1 g of gallium-indium alloy (gallium-indium, gallium mass ratio is 65%) is placed in 20 mL of distilled water, and 1.5 g of interface modifier 2,5-dithiodiurea is added to obtain a blend.
[0055] Ultrasonicate the blend for 30 minutes at 100% power of 600W probe ultrasound (15 seconds on, 15 seconds off working mode), remove 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend in the stop ultrasound state, repeat this process 3-4 times, and finally retain about 10 mL of the blend;
[0056] (3) The last remaining blend in step (2) is mixed with BNNSs in a container in proportion (specifically, the mass ratio of gallium indium to boron nitride nanosheets BNNSs in the blend is 1:3, wherein the mass of gallium indium in the blend is the gram weight of gallium indium in step (2), i.e., 1 g). The mixture is mixed and stirred in an aqueous phase at 60° C. for about 2 h to cause LM to adhere to the surface of BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs), referred to as a thermal conductive composite filler, is obtained.
[0057] The prepared gallium-indium alloy was mixed with the boron nitride nanosheet composite thermal conductive filler and polyurethane in a ratio of 7:3 to prepare a thermally conductive polyurethane composite material containing 30 wt % of the thermally conductive composite filler, referred to as the thermally conductive composite material. The preparation method was the same as that in Example 1.
[0058] Embodiment 4:
[0059] (1) 5 g of hexagonal boron nitride (BN) was placed in a mixture of 100 mL of N,N-dimethylformamide (DMF) and distilled water in a ratio of 1:2 (volume ratio), 4 mL of intercalation agent hexanediol was added, and ultrasonic exfoliation was performed at room temperature for 4 hours at a power of 500 W. The boron nitride nanosheets (BNNSs) after ultrasonic exfoliation were collected by filtration, rinsed with distilled water, and dried at 60 °C for later use;
[0060] (2) 1 g of gallium-indium alloy (gallium-indium-tin, the mass ratio of gallium-indium-tin is 62:15:13) is placed in 20 mL of distilled water, and 1.5 g of interface modifier thiourea is added to obtain a blend.
[0061] Ultrasonicate the blend for 30 minutes at 100% power of 600W probe ultrasound (15 seconds on, 15 seconds off working mode), extract 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend in the stop ultrasound state, repeat this process 3-4 times, and finally retain about 10 mL of the blend;
[0062] (3) The last remaining blend in step (2) is mixed with BNNSs in a container in proportion (specifically, the mass ratio of gallium indium tin to boron nitride nanosheets BNNSs in the blend is 1:2.2, wherein the mass of gallium indium tin in the blend is the gram weight of gallium indium tin in step (2), i.e., 1 g). The mixture is mixed and stirred in an aqueous phase at 60° C. for about 2 hours to cause gallium indium tin to adhere to the surface of BNNSs in the form of microspheres, and finally, after the water evaporates, a high thermal conductivity gallium indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs), referred to as a thermal conductive composite filler, is obtained. Figure 1 The SEM and SEM-mapping images of the thermally conductive composite filler prepared in Example 4 of the present invention are as follows: Figure 1 As shown, GaInT is implanted on the surface of boron nitride nanosheets (BNNSs) in the form of nano-particles, which are dispersed evenly and stably.
[0063] The prepared gallium-indium alloy was mixed with the boron nitride nanosheet composite thermal conductive filler and polyurethane in a ratio of 7:3 to prepare a thermally conductive polyurethane composite material containing 30 wt % of the thermally conductive composite filler, referred to as the thermally conductive composite material. The preparation method was the same as that in Example 1.
[0064] Comparative Example 1: Commercially available 400 micron boron nitride nanosheets (BNNSs) and polyurethane were mixed in a ratio of 7:3 to prepare a thermally conductive polyurethane composite material containing 30wt% boron nitride nanosheets (BNNSs). The preparation method of the thermally conductive polyurethane composite material is similar to that in Example 1. The preparation process of the thermally conductive polyurethane composite material containing 30wt% boron nitride nanosheets (BNNSs): 7g of polyurethane was dissolved in its benign solvent (DMF), the amount of solvent was not more than about 2 times the volume of polyurethane, and stirred at 60°C until the polyurethane was completely dissolved, 3g of boron nitride nanosheets (BNNSs) was added to the polyurethane solution, stirred for about 30 minutes, transferred to a planetary disperser and dispersed for 30 minutes at 500 rpm, and taken out. The above-mentioned dispersed and mixed mixture was added with deionized water of about 4 times the volume of the polyurethane solvent under stirring at 300 rpm to promote the precipitation of the thermally conductive polyurethane composite material containing boron nitride nanosheets (BNNSs). The precipitated thermally conductive polyurethane composite material was dried and hot-pressed for standby use. (The preparation methods of other thermal conductive polyurethane composite materials containing different mass fractions of BNNSs are the same as the above, only the corresponding BNNSs filler mass is changed).
[0065] The performance comparison of Examples 1-4 and the comparative example is shown in Table 1.
[0066] Table 1, performance comparison:
[0067] <![CDATA[Thermal conductivity w.m -1 k -1 > Example 1 4.05 Example 2 3.96 Example 3 4.07 Example 4 4.01 Comparative Example 1 2.25
[0068] It can be seen from Table 1 that the thermally conductive polyurethane composite materials containing gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs) in Examples 1-4 have better thermal conductivity than the thermally conductive polyurethane composite materials containing boron nitride nanosheets (BNNSs) in Comparative Example 1.
[0069] Figure 2 The in-plane thermal conductivity of the thermally conductive polyurethane composite material prepared by a single 400-micron boron nitride nanosheet (BNNSs) filler in Comparative Example 1 is compared with the thermally conductive polyurethane composite material prepared by a high thermal conductivity gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler (LM-BNNSs) in Example 4. Figure 2 The horizontal axis is the mass ratio of filler (BNNSs or LM-BNNSs) to the total amount of corresponding filler and polyurethane, and the vertical axis is the thermal conductivity of the corresponding thermally conductive polyurethane composite material. Figure 2It can be seen that for different filling amounts of boron nitride nanosheets (BNNSs) and gallium-indium alloy and boron nitride nanosheet composite thermal conductive fillers (LM-BNNSs), the thermal conductivity of the thermally conductive polyurethane composite prepared by gallium-indium alloy and boron nitride nanosheet composite thermal conductive fillers (LM-BNNSs) is much greater than that of the thermally conductive polyurethane composite prepared by single boron nitride nanosheet (BNNSs) filler. That is, at the same thermal conductive filler mass ratio, the thermal conductivity of the composite thermal conductive filler (LM-BNNSs) is significantly due to the single boron nitride nanosheet (BNNSs) filler, and the gallium-indium alloy droplets have a significant bridging effect between BNNSs, which optimizes the phonon transmission channel.
[0070] The protection scope of the present invention includes but is not limited to the above embodiments. The protection scope of the present invention shall be based on the claims. Any replacement, deformation, and improvement of the technology that can be easily thought of by technicians in this field shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive composite filler, characterized in that: The steps include: Step (1), preparation of boron nitride nanosheets BNNSs: (1.1) Hexagonal boron nitride (BN) is placed in a mixed solvent of N,N-dimethylformamide (DMF) and distilled water in a certain proportion, an interfacial intercalation agent is added, and ultrasonic exfoliation is performed. After that, the boron nitride nanosheets (BNNSs) after ultrasonic exfoliation are collected by filtration, rinsed, and dried for later use; Step (2), blend preparation: (2.1) Gallium-indium alloy LM is placed in distilled water, and an interface modifier is added to obtain a blend; (2.2) ultrasonically treat the blend for a period of time, remove a certain volume of the upper layer of the blend when the ultrasonication is stopped, and then inject distilled water of the same volume as the removed clear liquid into the blend; (2.3) Repeat step (2.2) multiple times, and finally retain a certain volume of the blend; Step (3), preparation of the composite thermal conductive filler LM-BNNSs of gallium-indium alloy and boron nitride nanosheets: (3.1) The last retained blend in step (2.3) is mixed with boron nitride nanosheets BNNSs in a container in proportion, and the mixture is mixed and stirred in an aqueous phase under a certain temperature environment to cause the gallium-indium alloy LM to adhere to the surface of the boron nitride nanosheets BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs, referred to as a thermal conductive composite filler, is obtained.
2. The method for preparing a thermally conductive composite filler according to claim 1, characterized in that: The step (1) is specifically as follows: 5 g of hexagonal boron nitride BN was placed in 100 mL of a mixed solvent of N,N-dimethylformamide DMF and distilled water in a certain proportion, 4 mL of an interfacial intercalation agent was added, and ultrasonic stripping was performed at room temperature for 4 hours at a power of 500 W. After that, the boron nitride nanosheets BNNSs after ultrasonic stripping were collected by filtration, rinsed with distilled water, and dried at 60°C for use.
3. The method for preparing the thermally conductive composite filler according to claim 2, characterized in that: In the step (1), the co-blended solvent is a mixture of N,N-dimethylformamide (DMF) and distilled water in a volume ratio of 1:1-3.
4. The method for preparing a thermally conductive composite filler according to claim 2, characterized in that: In the step (1), the interfacial intercalant is a diol solvent.
5. The method for preparing the thermally conductive composite filler according to claim 2, characterized in that: The step (2) is specifically as follows: (2.1), 1 g of gallium-indium alloy LM was placed in 20 mL of distilled water, and 1.5 g of interface modifier was added to obtain a blend; (2.2) Ultrasonicate the blend for 30 minutes at 100% power using a 600W probe, specifically in a 15-second on and 15-second off mode; remove 10 mL of the upper layer of the blend and inject 10 mL of distilled water into the blend when the ultrasound is stopped; (2.3) Repeat step (2.2) 3-4 times, and finally retain 10 mL of the blend.
6. The method for preparing the thermally conductive composite filler according to claim 5, characterized in that: In the step (2), the gallium-indium alloy LM is gallium-indium or gallium-indium-tin, wherein the mass ratio of gallium is greater than 60%.
7. The method for preparing a thermally conductive composite filler according to claim 5, characterized in that: In the step (2), the interface modifier is one of 2,5-dithiodiurea and thiourea.
8. The method for preparing a thermally conductive composite filler according to claim 5, characterized in that: The step (3) is specifically as follows: The last retained blend in step (2.3) is mixed with boron nitride nanosheets BNNSs in a container in proportion, and the mixture is mixed and stirred in an aqueous phase at 60°C for 2 hours to cause the gallium-indium alloy LM to adhere to the surface of the boron nitride nanosheets BNNSs in the form of microspheres. Finally, after the water evaporates, a high thermal conductivity gallium-indium alloy and boron nitride nanosheet composite thermal conductive filler LM-BNNSs is obtained.
9. The method for preparing a thermally conductive composite filler according to claim 8, characterized in that: In the step (3), the gallium-indium alloy LM and the boron nitride nanosheets BNNSs in the blend are blended in a proportion so that the mass ratio is 1:2-3, wherein the mass of the gallium-indium alloy LM in the blend is the gram weight of the gallium-indium alloy LM in step (2.1).
10. A method for preparing a thermally conductive composite material, characterized in that: include: Dissolving polyurethane in a benign solvent, stirring at a certain temperature until the polyurethane is completely dissolved, to obtain a polyurethane solution; Adding the thermally conductive composite filler prepared by the preparation method according to any one of claims 1 to 9 into the polyurethane solution, stirring, then transferring to a planetary disperser for dispersion, taking out, and obtaining a dispersed and mixed mixture; Deionized water is added to the dispersed and mixed mixture under stirring to promote the precipitation of the thermally conductive polyurethane composite material. The precipitated thermally conductive polyurethane composite material is dried and hot-pressed to obtain a formed thermally conductive polyurethane composite material, referred to as a thermally conductive composite material.
Citation Information
Patent Citations
High-heat-conducting composite material as well as preparation and application thereof
CN111117063A
High-thermal-conductivity liquid metal / boron nitride composite material and preparation method thereof
CN114525117A
High-thermal-conductivity / electrical-conductivity polymer-based composite material with three-dimensional low-melting-point metal-based filler network and preparation thereof
CN115322556A
Flexible heat conduction pad and preparation method thereof
CN115403931A
Boron nitride grafted gold nanoparticle composite filler and preparation method of heat-conducting adhesive
CN115926674A
Cited By
Heat dissipation composite material, preparation method and application of heat dissipation composite material as chip heat dissipation material
CN122127880A
